1. FEATURES OF THE PUBLIC PROCUREMENT MARKET IN ROMANIA - Daniela PIRVU; Claudia STANCIU-TOLEA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2017)
The public procurement market in Romania has become increasingly important in recent years, in the context of the harmonization of the national legislation with the European one. Despite the progress made in recent years, public procurement in Romania continues to be a subject of concerns, due to frequent revisions of procurement regulations (secondary legislation). Absorption of EU funds is often delayed by the numerous complaints lodged by bidders. This paper aims at highlighting the features of the public procurement market in Romania, based on a complex analysis focused on the 2008-2016 period. The data analysis reveals the change in the structure of the public procurement market in Romania in the analysed period. We also notice a fluctuating dynamics of this market, under the impact of the economic factors, both internal and external.